An Expedited Intracranial Pressure Monitoring Protocol Following Spontaneous CSF Leak Repair. (14th August 2020) - McCormick, Justin P.; Tilak, Ashwini; Lampkin, H. Brooks; Thompson, Harrison M.; Miller, Peter L.; West, John M.; Cho, Do‐Yeon; Riley, Kristen O.; Grayson, Jessica W.; Woodworth, Bradford A.
Abstract : Objective: Spontaneous cerebrospinal fluid (CSF) leaks represent a unique subset of skull base pathology and require distinctive management. Perioperative evaluation and management of intracranial hypertension are essential in preventing further erosion of the skull base and development of recurrent leak. The objective of this study is to evaluate the safety and utility of an expedited protocol for recording and managing intracranial hypertension following endoscopic repair of spontaneous CSF leaks. Methods: Prospectively collected data was reviewed in patients undergoing endoscopic repair of spontaneous CSF leaks between January 2017 and March 2020. A standard intracranial pressure monitoring protocol was compared to an expedited protocol (EP), and data regarding the two groups was compared for leak location, short‐term success of skull base repair, complications, hospital length of stay, and cost‐based analysis. Results: Fifty‐five patients (standard protocol, n = 28 vs. EP, n = 27) were included in the study. Leak location was similar between cohorts, with the lateral recess being the most common locations in both groups (37.9% vs. 40.6%; P = .90). Postoperative complications (3.6% vs. 7.4%; P = .53) and ventriculoperitoneal shunt rate (32.1% vs. 22.2%; P = .41) were similar among cohorts. There was no difference in lumbar drain complications (0% vs. 7.4%; P = .14) or recurrent leak (7.1% vs. 0%; P = .16). Length of stay was shorter in the EP group [median(interquartile range): 3(1) vs. 2 (1); P < .01]. Total hospital charges were similar between groups (median (USD/$1, 000): 83.57 ± 49.58 vs. 83.93 ± 46.11; P = .18). Conclusion: An expedited monitoring protocol shortened hospital stay without increased risk of complications. Level of Evidence: III Laryngoscope, 131:E408–E412, 2021